Predictors of Adherence Among Patients With Multiple Sclerosis Using the BETACONNECT® Autoinjector: A Prospective Observational Cohort Study - Köhler, Wolfgang; Bayer-Gersmann, Kirsten; Neußer, Thomas; Schürks, Markus; Ziemssen, Tjalf (Frontiers in Neurology, 2021)
Background: In patients with multiple sclerosis (MS), non-adherence to disease-modifying drug therapy is associated with an increased rate of MS relapses. Early identification of patients at risk of non-adherence would allow provision of timely and individualized support. The aim of the BETAPREDICT study was to investigate potential predictors of adherence in patients with MS in Germany treated with interferon β-1b (IFNβ-1b) using the BETACONNECT® autoinjector. Methods: BETAPREDICT was a national, multi-center, prospective, non-interventional, single-arm, 24-month cohort study of patients with relapsing–remitting MS or clinically isolated syndrome receiving IFNβ-1b via the BETACONNECT® autoinjector (ClinicalTrials.gov: NCT02486640). Injection data were captured by the autoinjector. The primary objective was to determine baseline predictors of compliance, persistence, and adherence to IFNβ-1b treatment after 12- and 24 months using multivariable-adjusted regression. Secondary objectives included evaluation of satisfaction with the autoinjector, injection site pain, vitamin and nutrient supplementation, clinical course, and patient-related outcome measures. Results: Of 165 patients enrolled, 153 were available for analysis (120 with autoinjector data). Seventy-two patients left the study prematurely. Compliance (N = 120), persistence (N = 153), and adherence (N = 120) at 24 months were 89.1%, 53.6%, and 41.7%, respectively. Compliance at 12- and 24 months was predicted by intake of vitamin D supplements and absence of specific injection site reactions. Positive predictors of persistence included age (at 12- and 24 months) and previous duration of treatment (at 12 months), while intake of vitamins/nutrients other than vitamin D was a negative predictor (at 12 months). Positive predictors of adherence at 24 months were age and being experienced with IFNβ-1b. Higher scores in specific SF-36 subscales were positive predictors of medication-taking behavior at 24 months. Satisfaction with the autoinjector was high at baseline and 24 months (median score: 9 out of 10). Conclusions: Compliance with IFNβ-1b treatment among participants still under observation remained high over a 24-month period, while persistence and adherence continuously declined. Multiple factors affected medication-taking behavior, including patient characteristics, treatment history, injection site reactions, patients’ perception of their health and support programs. The importance of these factors may differ among patients according to their individual situation.